THE USE OF DOMINO CARDS AS TEACHING MEDIA OF DESCRIPTIVE TEXT AT SMP N 6 WONOGIRI - Byantara Cantaka Mayestiendra Aji (ELT Worldwide: Journal of English Language Teaching, 2021)
This study explains how the teachers used domino cards in teaching descriptive text at SMP 6 Wonogiri. This type of research is descriptive qualitative. The subjects of this study were teachers and students of SMP 6 Wonogiri with 2 teachers and 6 students.This study uses interview and observation techniques in data collection. The results of this study indicate that the implementation of teaching descriptive text using domino cards improved students’ vocabulary mastery, student enthusiastic in learning process and fluency in writing descriptive text.  However, there were several difficulties faced by the students as expressed by as follows: 1) the students had limited vocabulary and a tenses. 2) The students were unfamiliar with and never used domino cards before. 3) The students found it difficult to understand the instructions given. Although experiencing some difficulties, the students felt happy and enthusiastic about the domino cards as teaching media in learning descriptive texts.